COMMUNITY LIFE “KAMPUNG BALI” REVIEW FROM SOCIAL, ECONOMIC AND CULTURAL ASPECTS (STUDY IN PATOMAN VILLAGE, BLIMBINGSARI DISTRICT, BANYUWANGI DISTRICT) - Dhalia Soetopo; Miskawi; Hanaul Vera Fatehah (International Jurnal of Education Schoolars, 2020)
Kampung Bali is an inland area located in Patoman Village, Blimbingsari District, Banyuwangi Regency in the midst of cultural, religious, ethnic and linguistic diversity, but can live side by side with one another. The topics of the problem in this research are: (1) The history of the existence of Kampung Bali in Patoman Village, Blimbingsari District, Banyuwangi Regency, (2) The Social, Economic and Cultural Life of Kampung Bali in Patoman Village, Blimbingsari District, Banyuwangi Regency, (3) Community efforts Kampung Bali in Banyuwangi Regency in preserving Balinese culture. The method used is a qualitative descriptive method with data collection techniques of observation, interviews, and documentation. The theory used in analyzing this research is Talcott Parsons' theory of Structural Functionalism. The results of this study indicate that (1) the history of the existence of the Balinese village is divided into three waves, namely wave I, there was upheaval during the Blambangan kingdom, waves II & III occurred during the eruption of Mount Agung, (2) the Balinese village community was able to adapt to maintain its sustainability both in terms social, economic and cultural. (3) The efforts of the people of Kampung Bali to preserve Balinese culture include the holding of PKB, the existence of a school for Balinese arts and culture, socialization to youth about Balinese customs and culture, the formation of the Youth Union in the Balinese village called Peradah (Indonesian Hindu Dharma Association).